Kewenangan Badan Penyelesaian Sengketa Konsumen (BPSK) dan Pengadilan Tuntutan Pengguna Malaysia (TTPM) dalam Penyelesaian Sengketa Konsumen - Ahmad Wahidi; Mustaklima Mustaklima; Nur Jannani (Jurnal Penelitian Hukum De Jure, 2023)
The violation of consumer rights is the cause of disputes. Consumer disputes are defined as disputes between the consumers and business actors in which consumers demand compensation due to damage, pollution, and/ or because of consuming products sold by business actors. The existing conditions of Malaysian consumers, consumer dispute resolution in Malaysia and its regulations, which are undergoing improvements, are rational reasons for the subject of comparison. The purpose of this study is to explore the factors behind the success of consumer dispute resolution in Malaysia, in this case the Tribunal Tuntutan Pengguna Malaysia (TTPM) from the side of its authority that can be adopted in Indonesia to reconstruct the Badan Penyelesaian Sengketa Konsumen (BPSK) so that it can be more successful in resolve consumer disputes. The results show that TTPM’s authority is more specific on dispute resolution and only accepts claims with definite value limitations, while BPSK’s authority has no limitations on the value of claims, the limitation on the value of compensation is only in the provision of administrative sanctions to business actors, for parties (business actors) who do not comply with the BPSK decision, the BPSK decision is the initial evidence for carrying out an investigation regarding whether there was a crime in the non-compliance. Meanwhile, non-compliance with the TTPM decision has been considered a criminal act with criminal sanctions of imprisonment and fines.